Polarisation and the news media in Europe - Fletcher, R; Jenkins, J (European Parliament, 2019)
This report describes a review of the literature examining the effect of news use on polarisation across Europe. In considering work concerned with both the supply side of news (news production) and the demand side (news consumption), the report concludes that across Europe there is as yet little evidence to support the idea that increased exposure to news featuring like-minded or opposing views leads to the widespread polarisation of attitudes. However, given that only a handful of studies have addressed this issue directly, there are large gaps in our knowledge concerning the situation in different European countries.